PENGEMBANGAN DAYA TARIK WISATA PURA KANCING GUMI BERBASIS WISATA BUDAYA, LINGKUNGAN PERMUKIMAN, DAN RELIGI DI DESA SULANGAI, PETANG-BADUNG - Anak Agung Gede Raka Gunawarman (Lentera Karya Edukasi, 2021)
Sulangai Village as a village located in Petang District, Badung Regency, Bali is a village that is rich in its natural panorama. Seeing how the potential for increasing tourist visits to Bali, and the existence of a village-based tourism development policy, Sulangai Village through the village government seeks to direct the development of the village into a tourist destination by developing natural cultural tourism potential points in the village area.Kancing Gumi Temple is one of the tourist attraction points in Sulangai Village based on religious tourism, residential environments, and culture. The potential of the tourist attraction of the Kancing Gumi Temple in Sulangai Village is divided into three categories, namely: (1) the potential of the Kancing Gumi Temple as a religious tourism destination; (2) Residential Environment. The problem of the readiness of these supporting facilities as a complement and a means to carry out tourism activities in Sulangai Village is certainly a fundamental reason for this PKM activity to be carried out. Of course, some of the solutions offered will be related to the field of science of the implementing team, namely providing ideas or ideas in the form of planning and designing of any supporting facility needs that are considered to be a priority part. The outputs of this PKM are in the form of a Community Service Journal, online mass media publications, IPR, and video publications via YouTube.